Categorization of Coconut Milk Products by Their Sensory Characteristics - Wattanapahu, Saowapark; Suwonsichon, Thongchai; Jirapakkul, Wannee; Kasermsumran, Sumaporn (Agriculture and Natural Resources, 2012)
Coconut milk is extensively used as a major ingredient of savory foods and desserts in many countries. The sensory characteristics of coconut milk have a substantial effect on consumer acceptance. The objectives of this investigation were to develop a lexicon of coconut milk products produced by different tempering processes and to categorize coconut milk products based on their sensory properties. Twelve samples consisting of two unheated, four pasteurized, three UHT, one sterilized and two spray dried were collected and determined. Eight highly trained panelists described the sensory characteristics of the coconut milk samples. The results demonstrated that there were 17 attributes: smoothness, overall coconut milk odor, sweetness of coconut milk odor, freshness odor, coconut oil odor, cooked odor nutty odor, overall coconut milk ﬂ avor, freshness ﬂ avor, oily ﬂ avor, cooked ﬂ avor, sweet ﬂ avor, nutty ﬂ avor, viscosity, fat feel, dryness, lip and mouth feel. All 17 sensory attributes were signiﬁ cantly different (P < 0.05) among coconut milk samples. The results of hierarchical cluster analysis (HCA) and principal component analysis (PCA) demonstrated that PCA reduced the 17 sensory attributes into two independent principal components (PCs), which accounted for 87.30% of the explained variance. These two PCs with HCA could classify the 12 samples into ﬁ ve groups related to their tempering processes.